Interleukin-12 (IL-12p70) Promotes Induction of Highly Potent Th1-Like CD4+CD25+ T Regulatory Cells That Inhibit Allograft Rejection in Unmodified Recipients - Verma, Nirupama Darshan; Hall, Bruce Milne; Plain, Karren Michelle; Robinson, Catherine M.; Boyd, Rochelle; Tran, Giang T.; Wang, Chuanmin; Bishop, G. Alex; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2014)
In rat models, CD4+CD25+ T regulatory cells (Treg) play a key role in the induction and maintenance of antigen-specific transplant tolerance, especially in DA rats with PVG cardiac allografts (1, 2). We have previously described generation of alloantigen-specific Treg (Ts1), by culture of naïve natural CD4+CD25+ Treg (nTreg) with specific alloantigen and IL-2 for 4 days. These cells express mRNA for IFN-γ receptor (ifngr) and suppress donor but not third party cardiac allograft rejection mediated by alloreactive CD4+ T cells at ratios of <1:10. Here, we show that Ts1 also expressed the IL-12p70 specific receptor (il-12rβ2) and that rIL-12p70 can induce their proliferation. Ts1 cells re-cultured with rIL-12p70 alone or rIL-12p70 and recombinant interleukin-2 (rIL-2), suppressed proliferation of CD4+ T cells in mixed lymphocyte culture at <1:1024, whereas Ts1 cells re-cultured with rIL-2 and alloantigen only suppressed at 1:32–64. The rIL-12p70 alloactivated Ts1 cells markedly delayed PVG, but not third party Lewis, cardiac allograft rejection in normal DA recipients. Ts1 cells re-cultured for 4 days with rIL-12p70 alone, but not those re-cultured with rIL-12p70 and rIL-2, expressed more il-12rβ2, t-bet, and ifn-γ, and continued to express the markers of Ts1 cells, foxp3, ifngr, and il-5 indicating Th1-like Treg were induced. Ts1 cells re-cultured with rIL-2 and alloantigen remained of the Ts1 phenotype and did not suppress cardiac graft rejection in normal DA rats. We induced highly suppressive Th1-like Treg from naïve nTreg in 7 days by culture with alloantigen, first with rIL-2 then with rIL-12p70. These Th1-like Treg delayed specific donor allograft rejection demonstrating therapeutic potential.